1984
DOI: 10.1557/proc-34-181
|View full text |Cite
|
Sign up to set email alerts
|

Computer Simulation of Solidification of Nodular Cast Iron

Abstract: Solidification of a nodular iron casting was simulated byanundercooling nucleation and diffusion controlled growth model. Simulated cooling curves were similar to measured ones but estimating nodular size distribution requires improving the model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 1 publication
0
21
0
Order By: Relevance
“…Dardati et al 20 compared one model based on the uninodular theory by Su et al 7 and two models based on the multinodular theory presented in Boeri 18 and Dardati et al 21 In terms of nodule count the three models showed very similar results with each other and showed a good agreement with the experimental ones. Regarding the cooling curves, the slope of the model developed by Dardati et al 21 differs from the experimental one during the first cooling stage and also shows the smallest undercooling compared with the other two models and with the experimental one.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…Dardati et al 20 compared one model based on the uninodular theory by Su et al 7 and two models based on the multinodular theory presented in Boeri 18 and Dardati et al 21 In terms of nodule count the three models showed very similar results with each other and showed a good agreement with the experimental ones. Regarding the cooling curves, the slope of the model developed by Dardati et al 21 differs from the experimental one during the first cooling stage and also shows the smallest undercooling compared with the other two models and with the experimental one.…”
mentioning
confidence: 84%
“…It is widely accepted that the growth kinetics of nodular cast iron is primarily controlled by solid state diffusion of carbon through the austenite shell. 6,7 Two models based on either deterministic laws or stochastic procedures describe the growth mechanism and the solidification process of eutectic nodular cast iron: uninodular [7][8][9][10][11][12][13][14][15][16] and multinodular [17][18][19][20][21] models. The former considers that spherical graphite nuclei are immediately enveloped by an austenite shell and subsequent growth occurs by carbon diffusion through this envelope.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several models have been proposed to describe the kinetic mechanisms that occur during the liquid-solid transformation of a SGCI with eutectic composition, some of them being based on the uninodular theory [5][6][7][8][9][10][11][12][13][14] and others based on the multinodular theory [15][16][17][18][19]. Nevertheless, the so-called multinodular models are nowadays gaining acceptance due to their good prediction capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Castings made of this material not only have a low weight, but also very good mechanical properties [3][4][5]. For this reason, nodular graphite cast iron continues being the object of studies using different mathematical models, the main task of which is the best approximation of processes that occur during crystallisation of this alloy [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%